Diagnostic and prognostic characteristics of phytotoxicity caused by fluoride on Spondias dulcis Forst. F. (Anacardiaceae) - Bruno F. Sant'Anna-Santos; Aristéa A. Azevedo; Luzimar C. Silva; Marco A. Oliva (Anais da Academia Brasileira de Ciências, 2012)
The goal of this study was to determine the symptoms and microscopic damage caused by fluoride on Spondias dulcis, a fluoride-sensitive species. The plants were exposed to simulated fog with fluoride (0, 5, 10, 15 and 20 mg L-1) for 20 min daily during four consecutive days. Samples from leaflets without any apparent fluoride injury were collected to microscopic analysis. The percentage of necrosed leaf area was measured, and the level of pollutant in the dry matter from the basal and apical portions of the plant was determined. The necroses began 24 h after the first simulation mainly from the base of the leaflets. A higher level of necrosis was observed at the apical portion of the plants, a region of higher fluoride accumulation. The damage on the surface of the leaflets was characterized as plasmolysis, erosion of the epicuticular waxes and epidermal rupture. Structurally, the noticeable accumulation of granules and droplets green stained by toluidine blue in the spongy parenchima and the boundaries of ending veinlets was observed. The limb thickness reduction occurred due to plasmolysis in the mesophyll, showing an apparent correlation with the damage observed on the surface. The parameters observed in the laboratory are promising for field biomonitoring studies. O objetivo deste estudo foi determinar os sintomas e danos microscópicos causadas pelo flúor em Spondias dulcis, espécie sensível a essa substância. As plantas foram expostas a nevoeiros simulados com flúor (0, 5, 10, 15 e 20 mg L-1) por 20 minutos diários, durante quatro dias consecutivos. Amostras de folíolos sem qualquer lesão aparente ao flúor foram coletadas para análise microscópica. Mensurou-se a percentagem de área foliar necrosada e o teor do poluente na matéria seca das porções basal e apical da planta. As necroses surgiram 24 horas após a primeira simulação e tiveram início, principalmente, a partir da base dos folíolos. As necroses foram mais severas na porção apical das plantas, região com maior acúmulo de flúor. O dano na superfície dos folíolos foi caracterizado como plasmólise, erosão das ceras epicuticulares e ruptura da epiderme. Estruturalmente, observou-se considerável acúmulo de grânulos e gotas coradas de verde pelo azul de toluidina no parênquima lacunoso e nas proximidades das terminações xilemáticas. Houve redução da espessura do limbo devido a plasmólise no mesofilo, havendo aparente correlação com os danos observados na superfície. Os parâmetros observados em laboratório são promissores para estudos de biomonitoramento em campo.